Ethiopia : Country Assistance Evaluation, 1998-2006 - Thomas, Vinod (World Bank, Washington, DC, 2012)
Ethiopia is among the World Bank's largest IDA-eligible borrowers in Sub-Saharan Africa, with a country portfolio comprising 22 active projects for a total net commitment of US$2 billion as of end-FY07. The Bank's overarching objective during the period under review (FY98-FY06) was to support the Government in its efforts to reduce poverty by helping to: (i) promote pro-poor growth; (ii) advance private sector development; (iii) enhance human development; (iv) respond to the needs of post-conflict and emergency rehabilitation; and (v) improve governance. The evaluation finds that IDA's country strategy for Ethiopia and the associated program during the period under review were relevant to the country's development needs, which included the need to manage (and over time reduce the country's exposure to) frequent exogenous shocks and a fragile socio-political environment, especially following the post-election violence in 2005. IDA's strategy and program were also aligned with those of other development partners (DPs). The efficacy of the program was somewhat below average when measured against the goals envisaged at the outset. There were positive outcomes inter alia in post-conflict rehabilitation, economic growth, roads development, education and health. In contrast, the outcomes were less favorable in the key areas of private sector development and governance, which are crucial to sustaining growth over the longer-term and ensuring that its benefits are widely shared.